Platelet-rich plasma (PRP) for the treatment of muscle injury / Mohamad Shariff A Hamid - Mohamad Shariff, A Hamid (2014)
Muscle injury particularly the hamstring group is the most common type of sports related injury among athletes. Despite its frequent occurrence, the best treatment for hamstring injury is not known. Athletes affected by muscle injury often need considerable amount of time to recover. Recently autologous biological products are being used for treatment of soft tissue injury including that of muscles. Off recent, an autologous platelet-rich plasma (PRP) therapy is one of the ‘hot topics’ discussed in literatures. A systematic review of the available literatures on PRP therapy showed evidences to support PRP use for rotator cuff injury, lateral epicondylitis (tennis elbow), patellar tendinopathies and Achilles' tendinopathies. As clinical evidence to support its usefulness is limited, a randomised controlled trial is needed to examine the effect of PRP on muscle injury. Besides, current evidences were based on few laboratory animal studies and case reports. Since information on injury prevalence and management of muscle injury in the local settings is limited, a cross-sectional study was conducted to investigate the pattern of muscle injury among Malaysian athletes. Medical records of athletes diagnosed with muscle injury were examined and injury mechanisms, types, treatment and duration to return-to-play (DRP) recorded. The pattern of muscle injury among Malaysian athletes was comparable to those reported by earlier researchers. Surprisingly, the DRP of local athletes were considerably longer compared with other studies (7.4 versus 3.8 weeks). Further, duration before first consultation, recurrent hamstring injury and female athletes were significant predictors of DRP. The decision to allow return-to-play was based on athlete’s symptoms of pain and objective clinical assessments including muscle flexibility test. An active knee extension (AKE) test was designed for assessment of hamstring flexibility in the RCT. A preliminary study on 14 healthy individuals showed excellent interater and test-retest reliabilities with intraclass correlation coefficient ranges from 0.78 to 0.92. This findings support the inclusion of the AKE test in the RCT. Twenty-eight athletes diagnosed with grade-2 acute hamstring injury were recruited in an RCT to explore effect of PRP on DRP. Both intervention and control groups were prescribed with a standard rehabilitation program. Additionally patients in the PRP group received a single 3 ml injection of autologous PRP (approximately 5-fold increase in platelets and white blood cells) into the injured muscle. Significantly earlier DRP (p = 0.013) was noted among participants in the PRP (median 21.0 ± IQR 13.0 days) compared with control (median 34.0 ± IQR 37.3 days). In addition the PRP group has significantly (p ≤ 0.001) lower pain severity score (1.14 ± SE 0.19) than control at all time points (2.31 ± SE 0.23). Furthermore participants reported no severe adverse effect of PRP therapy. In conclusion the findings of this research suggest PRP therapy is a safe and effective treatment for muscle injury.